Фазовый состав, структура и механические свойства богатых титаном сплавов системы Ti–Dy–Sn - Буланова, М.В.; Подрезов, Ю.Н.; Фартушная, Ю.В.; Рафал, А.Н.; Фирстов, С.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The phase composition, structure, and mechanical properties of Ti-rich alloys of the Ti–Dy–Sn system are studied. It is shown that plasticity at 20 °C of as-cast and annealed Ti–Dy–Sn alloys decreases versus tin concentration. The concentration dependence of plasticity at 800 °C of as-cast and annealed alloys shows the maximum at 10–15% (аt.) Sn. The values of yield stress and ultimate stress at 20 and 800 °C of both as-cast and annealed alloys demonstrate the maxima at 10–15% (аt.) tin, as well. This corresponds to the <β*–Ti>+<Dy5Sn3>/<β*–Ti>+<Ti3Sn>+<Dy5Sn3> phase boundary.